Community-based tourism initiative in rural Malaysia: is it a success? - Kayat, Kalsom; Zainuddin, Nur Farrah Ain (2016)
This study explores the success criteria for Malaysia Homestay Program (MHP), which is a community-based rural tourism initiative promoted by the government.The goals of this initiative are to empower rural communities through their engagement in rural tourism activities as well as to increase visitor arrivals to rural destinations in Malaysia. The establishment of its success criteria is critical as the criteria can be used to measure the performance of the initiative. Amid the publicized statistics for visitor arrival to the homestay programs under MHP, evidence of their true performance and success as a community-based tourism (CBT) initiative is still scarce.In this study, experts who are familiar with MPH in their lines of work were asked to identify criteria which are regarded by them as crucial for an MPH program to be successful.Their responses were analyzed to establish the success criteria of the programs and to determine if their responses mirror the conditions of CBTs mentioned in the literature.Findings from the responses indicate that the successful criteria of the MPH programs can be grouped into the competitive criteria and the sustainability criteria.